PERBANYAKAN VEGETATIF TUSAM (Pinus merkusii Jungh et de Vriese) DENGAN TEKNIK CANGKOK - Suryanaji; Purwanto, Purwanto; Pramudita, Arga (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Pinus merkusii is a main species for produce pine resin in Indonesia. Clone of Pinus merkusii on progeny trial establishing by Perhutani has identified can produce high yielderresin up to 100 gr/tree/3 days. Clonal forestry needs applied propagation method that easy dan economically on operational level. One of propagation method selected was by air layering. This research work were to obtained genetic materials and to get information number of live percent of seedling from air layering from high yielder resin Pinus merkusii subline when the mother trees reach 12 years old. The research was conducted in Perum Perhutani KPH Banyumas Barat, RPH Samudra on year 2020 with Completely Randomized Design (CRD). The result of this research showed that rooting ability on Pinus merkusii 12 years old mother trees have signifiant differences between subline. Rooting ability of seedling generated by air layering method were 29% (subline SG2), 24% (subline JB2), 18% (subline SL2) and 11% (subline SM2) with an average of 18% and heritability of rooting ability by air layering was 0,44.